Free-weight resistance exercise on pulse wave reflection and arterial stiffness between sexes in young, resistance-trained adults. Issue 8 (14th September 2017) - Kingsley, J. Derek; Tai, Yu Lun; Mayo, Xian; Glasgow, Alaina; Marshall, Erica
Abstract: We sought to determine the sex-specific effects of an acute bout of free-weight resistance exercise (RE) on pulse wave reflection (aortic blood pressures, augmentation index (AIx), AIx at 75 bpm (AIx@75), augmentation pressure (AP), time of the reflected wave (Tr), subendocardial viability ratio (SEVR)), and aortic arterial stiffness in resistance-trained individuals. Resistance-trained men ( n = 14) and women ( n = 12) volunteered to participate in the study. Measurements were taken in the supine position at rest, and 10 minutes after 3 sets of 10 repetitions at 75% 1-repetition maximum on the squat, bench press, and deadlift. A 2 × 2 × 2 ANOVA was used to analyse the effects of sex (men, women) across condition (RE, control) and time (rest, recovery). There were no differences between sexes across conditions and time. There was no effect of the RE on brachial or aortic blood pressures. There were significant condition × time interactions for AIx (rest: 12.1 ± 7.9%; recovery: 19.9 ± 10.5%, p = .003), AIx@75 (rest: 5.3 ± 7.9%; recovery: 24.5 ± 14.3%, p = .0001), AP (rest: 4.9 ± 2.8 mmHg; recovery: 8.3 ± 6.0 mmHg, p = .004), and aortic arterial stiffness (rest: 5.3 ± 0.6 ms; recovery: 5.9 ± 0.7 ms, p = .02) with significant increases during recovery from the acute RE. There was also a significant condition × time for time of the reflected wave (rest: 150 ± 7 ms; recovery: 147 ± 9 ms, p = .02) and SEVR (rest: 147 ± 17%; recovery: 83 ± 24%, p = .0001) such that they were reduced during recovery from the acute RE compared to the control. These data suggest that an acute bout of RE increases AIx, AIx@75, and aortic arterial stiffness similarly between men and women without significantly altering aortic blood pressures.